2017
DOI: 10.1101/139238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novomutations implicate novel genes with burden of rare variants in Systemic Lupus Erythematosus

Abstract: The omnigenic model of complex diseases stipulates that the majority of the heritability will be explained by the effects of common variation on genes in the periphery of core disease pathways. Rare variant associations, expected to explain far less of the heritability, may be enriched in core disease genes and thus will be instrumental in the understanding of complex disease pathogenesis and their potential therapeutic targets. Here, using complementary whole-exome sequencing (WES), high-density imputation, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Next generation sequencing (NGS) technologies, including whole genome sequencing (WGS) and whole exome sequencing (WES), have led to increasing recognition that rare/novel variants are more deleterious than common variants (25). A previous study explored rare variants by undertaking WES of SLE patients showed that 14 missense de-novo variants were identified in SLE probands (26). In recent years, more and more rare variants that cause SLE have been identified, such as novel peripheral gene MEF2D, germline rare P2RY8 missense variants and SAT1 LOF variants (27)(28)(29).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Next generation sequencing (NGS) technologies, including whole genome sequencing (WGS) and whole exome sequencing (WES), have led to increasing recognition that rare/novel variants are more deleterious than common variants (25). A previous study explored rare variants by undertaking WES of SLE patients showed that 14 missense de-novo variants were identified in SLE probands (26). In recent years, more and more rare variants that cause SLE have been identified, such as novel peripheral gene MEF2D, germline rare P2RY8 missense variants and SAT1 LOF variants (27)(28)(29).…”
Section: Genetic Factorsmentioning
confidence: 99%